An Immersive and Interactive Setting to Practice Emotional Intelligence - Bertagni, Barbara; Gardner, Roxane; Minehart, Rebecca; Salvetti, Fernando (International Journal of Advanced Corporate Learning (iJAC), 2023)
Emotions are an essential part of being human. Whether we experience them deeply, overcontrol them, or let them overwhelm us, emotions have a big influence on our experiences, our performance, and our quality of life. Bing emotional intelligent helps us make better decisions, forge stronger relationships, and overcome challenging situations. To improve emotional intelligence, we designed an immersive setting where participants interact with a variety of situations digitally displayed with fully cognitive and emotional involvement practicing empathy, self-awareness, and self-regulation. We work at the inter- section of thinking and feeling, increasing participants’ awareness about the way the mind works, experimenting the intensity of the emotions in the body and the impact on the behavior. Scientific evidence from neuroscience shows that as human beings, we are not passive receivers of sensory input, but our brain constructs meaning actively from sensory input, beliefs, past experiences, and culture. In our brains, thoughts and feelings are highly interconnected: we feel what our brain believes, so reflection on emotion is crucial to make sense of our experiences and regulate our feelings. It’s not about controlling emo- tions, but rather about connecting with our emotional life.